Effect of drying temperature on Malaysia pomelo (Citrus grandis (L.) Osbeck) pomace residue under vacuum condition - Abd Rahman, Nur Farhana; Ismail, Amin; Abdul Karim Shah, Nor Nadiah; Varith, Jaturapatr; Shamsudin, Rosnah (Universiti Putra Malaysia Press, 2019)
Pomelo pomace (PP) from Malaysia Tambun White (PO52) variety, dried at different temperature under vacuum condition were evaluated. PP was obtained after extraction process and contained high moisture content (MC). Dried PP can be used as an alternative to livestock feed, hence, dried concentrated form was preferable. Nevertheless, drying process significantly affects the physico-chemical properties of a dried product. Therefore, the present study was carried out to discover the effects of drying temperature on the physico-chemical properties (MC, pH, vitamin C, browning index (BI) and total color change) of PP. The PP was dried at different drying temperature (50, 60, 70, 80 and 90°C) using a vacuum drying (VD) oven for 24 hr. The freeze drying (FD) process was used as a control. The result showed the MC gradually decreased with increasing drying temperature, of which similar trend was also observed for the water activity and total soluble solids (TSS). In contrast, pH showed increment in value with elevated drying temperature. Interestingly, at 90°C, vitamin C of VD (30.38 mg / 100 g DW) was higher than FD pomelo pomace (21.10 mg / 100 g DW). BI significantly increased as temperature increased. However, no significant changes were observed for total color change after VD. In conclusion, VD at 90°C showed the most recommended temperature because the composition of quality properties at this temperature was not significantly varied with control. These fundamentals information of pomelo pomace could be the guideline for postharvest technologist and food processing manufacturers for various applications.